Skin Changes Seem in Pregnancy and Analysis of the Dermatoses of Pregnancy - Dertlioğlu, Selma BAKAR; Çiçek, Demet; Uçak, Haydar; Çelik, Hüsnü; Halisdemir, Nurhan (Fırat University, 2011)
Objective: This study was performed to ascertain the clinical characteristics of cutaneous changes in pregnancy and spesific dermatoses of pregnancy. Materials and Methods: A total of 135 pregnant women who were treated in gynecology clinic of obstetric service in Firat University were included in this study. Detailed history and dermatological examination were done. Informed consent was obtained before the clinical examination. Skin lesions were recorded and photographed. Appropriate investigations like histopathological and immunohistochemical examination of skin biopsy were done to confirm diagnosis if required. Results: This study included 17-49 year-old 135 pregnant women. Forty-nine of the women were primigravid and 86 of them were multigravid. The mean age was 31.9±7.6 years. The most common physiological skin changes were detected respectively; 81(60%) striae gravidarum, 77 (57%) kloazma and 58 (43%) gingival changes. The frequency of prurigo of pregnancy was determined as 20 (14.8%), polymorphic eruption of pregnancy was 12 (8.9%) and intrahepatic cholestasis of pregnant was 1 (0.7%) of pregnant women. Especially in the development of polymorphic eruption of pregnancy was significantly higher in the third trimester. There was significantly difference between polymorphic eruption of pregnancy and prurigo of pregnancy in terms of the pregnancy week (p=0.003). Conclusion: As a result, we found that a large number of physiologic and pathologic skin changes during pregnancy. While some of these changes were related to pregnancy women's age the other of them were related to pregnancy week and number.

Amaç: Bu çalışmanın amacı gebeliğe özgü deri bulguları ve gebelik dermatozlarını araştırmaktır. Gereç ve Yöntem: Bu çalışmaya Fırat Üniversitesi Kadın Hastalıkları ve Doğum Ana Bilim Dalı Obstetri Servisi'nde yatarak tedavi gören 135 gebe alındı. Gebelerin anamnezleri alınarak, dermatolojik muayeneleri yapıldı. Onayları alınan gebelerin sistemik ve cilt bulguları kaydedilerek fotoğraflandı. Gerekli durumlarda cilt biyopsisi alınarak histopatolojik ve immünohistokimyasal incelemeler yapıldı. Bulgular: Bu çalışma yaşları 17-49 arasında olan 135 gebeyi içermektedir. Gebelerin 49'u primigravid, 86'sı multigravid olup yaş ortalamaları 31.9±7.6 yıl idi. Gebelerde saptadığımız en sık fizyolojik deri değişikliği sırasıyla: 81 (%60) stria gravidarum, 77 (%57) kloazma ve 58 (%43) dişeti değişiklikleri idi. Gebeliğe özgü dermatozlardan 20 gebede (%14.8) gebelik prurigosu (GP), 12'sinde (%8.9) gebeliğin polimorfik erüpsiyonu (GPE) ve 1'inde (%0.7) gebeliğin intrahepatik kolestazı (GİK) tespit edildi. GPE gelişiminin özellikle 3. trimesterde anlamlı düzeyde yüksek olduğu gözlendi. GPE ile PG arasında gebelik haftası açısından anlamlı bir farklılık mevcuttu (p=0.003). Sonuç: Sonuç olarak gebelerde çok sayıda fizyolojik olan ve olmayan deri bulgusu saptadık. Bu değişikliklerin bazılarının hastaların yaşı ile bazılarının ise gebelik sayısı ve gebelik haftası ile ilişkili olarak ortaya çıktığı sonucuna vardık.
Gebelikte Gözlenen Deri Değişiklikleri ve Gebelik Dermatozlarının İncelenmesi